2018
DOI: 10.1515/pjfns-2017-0029
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR-Based Metabolic Profiling of Urine from Mice Fed Lentinula edodes-Derived Polysaccharides

Abstract: of the most important components responsible for the bioactivities of L. edodes. In our previous studies, a new type of heteropolysaccharide, named L2, was obtained from the fruit body of L. edodes with an average molecular weight of 26 KDa but without triple-helix conformation [Xu et al., 2012]. In vitro, L2 increased the production of nitric oxide, tumor necrosis factor α, and interleukin 6 of RAW 264.7 cells in a wide range of pH circumstances with the involvement of toll-like receptor 2 [Xu et al., 2012]. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In Asian countries, shiitake mushroom ( Lentinus edodes ) is one of the most economically important varieties of edible mushrooms owing to its unique flavor and texture. Furthermore, shiitake mushrooms have many beneficial effects on human health, including antitumor (Ya, 2017), antiaging (Xu et al., 2017), and antioxidant effects (Zhu et al., 2018). Expansion of the supply chain due to market globalization escalates the risk of prolonged exposure of fresh shiitake mushrooms to vibrations occurring during transport.…”
Section: Introductionmentioning
confidence: 99%
“…In Asian countries, shiitake mushroom ( Lentinus edodes ) is one of the most economically important varieties of edible mushrooms owing to its unique flavor and texture. Furthermore, shiitake mushrooms have many beneficial effects on human health, including antitumor (Ya, 2017), antiaging (Xu et al., 2017), and antioxidant effects (Zhu et al., 2018). Expansion of the supply chain due to market globalization escalates the risk of prolonged exposure of fresh shiitake mushrooms to vibrations occurring during transport.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, L2 reduced the diversity and evenness of gut microbiota in adult mice while elevating the diversity and evenness of gut microbiota in aged mice [19,22]. Further urinary metabolomic analysis also confirmed the differential physiological impacts of L2 on adult and aged mice [78,79]. The differences also suggested that the regulatory mechanism might be bacterial-specific since gut microbiota could modulate the protein expression exhibiting hetero-phenotypes in multiple tissues in mice [80].…”
Section: Discussionmentioning
confidence: 79%
“…12 Betaine, or trimethylglycine, is an amino acid derivative that occurs naturally in plants and has anti-inflammatory, anti-aging, and moisturizing properties. 13,14 Betaine-based DESs have been developed to effectively extract catechins and flavanols from green tea and preserve the extract over a longer period of time compared to aqueous and organic solvent extractions. 15 We recently reported that natural products such as limonene and hibaene can be effectively extracted from Hinoki (Chamaecyparis obtusa) using betaine-based DESs.…”
mentioning
confidence: 99%